FRI0472 Correlations between Different Histological Subsets of GIANT Cell Arteritis and Clinical Manifestations in A Large Monocentric Cohort of Biopsy Positive GCA Patients. (10th June 2014) - Muratore, F.; Cavazza, A.; Restuccia, G.; Macchioni, P.; Germanò, G.; Pipitone, N.; Bajocchi, G.; Boiardi, L.; Salvarani, C.
Abstract : Background: Temporal artery biopsy (TAB) showing transmural inflammation is considered the gold standard for the diagnosis of giant cell arteritis (GCA). In some cases of GCA, inflammation is confined to the periadventitial small vessels, the vasa vasorum and/or the adventitia. These patients seem to closely resemble classic GCA, but the final significance of this more limited inflammation need more confirmation. Objectives: To describe and correlate different histological subsets of GCA with demographic and clinical manifestations in a large monocentric cohort of biopsy positive GCA patients. Methods: All TABs performed for suspected GCA between 1986 and 2012 were reviewed by a single pathologist. Based on the localization of the inflammation, positive TABs were classified into 4 categories: small vessel vasculitis (SVV), with inflammation limited to small periadventitial vessels devoid of muscular coat; vasa vasorum vasculitis (VVV), with inflammation surrounding the adventitial vasa vasorum; inflammation limited to adventitia (ILA), with inflammation spreading from vasa vasorum to the adventitia without extension to the media; transmural inflammation (TMI), with external elastic lamina disruption and extension of the inflammation to the media. Results: 317 TABs were positive for inflammation and were classified as: 253 (79.8%) TMI, 18 (5.7%) ILA, 19 (6.%) VVV and 27 (8.5%) SVV. Compared to patients with TMI, those with SVV and VVV had a significantly lower frequency of headache (55.6% vs 77.9%, p=0.010 for SVV and 57.9% vs 77.9%, p=0.048 for VVV), jaw claudication (7.4% vs 44.7%, p<0.0001 for SVV and 15.8% vs 44.7%, p=0.015 for VVV), abnormalities of TA at physical examination (33.3% vs 71.3%, p<0.0001 for SVV and 47.1% vs 71.3%, p=0.036 for VVV), halo at TA color duplex sonography (CDS) (27.3% vs 72.4%, p<0.0001 for SVV and 16.7% vs 72.4%, p<0.0001 for VVV), systemic symptoms (only for VVV, 42.1% vs 66.8%, p=0.029), a lower levels of ESR (70.4±30.9 vs 86.5±30.1, p=0.011 for SVV and 64.9±34.7 vs 86.5±30.1, p=0.010 for VVV, mean ± DS mm/hour) and CPR (7.4±8.4 vs 8.9±6.1, p=0.027 for SVV and 3.5±3.7 vs 8.9±6.1, p<0.0001 for VVV, mean ± DS mg/dl) an higher frequency of male gender (63% vs 22.1%, p<0.0001 for SVV and 42.1% vs 22.1%, p=0.048 for VVV) and peripheral arthritis (only for SVV, 22.2% vs 6%, p=0.002) but a similar frequency of polymyalgia rheumatica, large vessel involvement and visual symptoms (including blindness). Patients with ILA were more similar to those with TMI, showing only a lower frequency of headache (55.6% vs 77.9%, p=0.031), abnormalities of TA at physical examination (40% vs 71.3%, p=0.011) and halo at TA CDS (14.3% vs 72.4%, p=0.003). Conclusions: The histological spectrum of inflammatory lesions that can be found in TAB is broad and constitutes a continuum, ranging from SVV at one extreme, through VVV and the more spread ILA in the middle, to TMI at the other extreme of the spectrum. Despite the differences in cranial symptoms, halo sign at CDS and levels of acute-phase reactants, it is crucial that clinicians be aware that all different histologic TAB patterns are equally associated with a risk of visual loss, thus requiring prompt glucocorticoid treatment. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5674